2012
DOI: 10.1186/1472-6882-12-149
|View full text |Cite
|
Sign up to set email alerts
|

Kalanchoe tubiflora extract inhibits cell proliferation by affecting the mitotic apparatus

Abstract: BackgroundKalanchoe tubiflora (KT) is a succulent plant native to Madagascar, and is commonly used as a medicinal agent in Southern Brazil. The underlying mechanisms of tumor suppression are largely unexplored.MethodsCell viability and wound-healing were analyzed by MTT assay and scratch assay respectively. Cell cycle profiles were analyzed by FACS. Mitotic defects were analyzed by indirect immunofluoresence images.ResultsAn n-Butanol-soluble fraction of KT (KT-NB) was able to inhibit cell proliferation. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 64 publications
(62 reference statements)
1
13
0
Order By: Relevance
“…In contrast, higher activity was observed for the extract against human papillomavirus (HPV), which plays a pivotal role in the development of cervical cancer [87]. The butanol-soluble fraction of an ethanolic extract of fresh B. delagoense plants showed antiproliferative activity [88] in several cell lines via a modulation of the mitotic cell division. More recently, the water-soluble fraction of the same extract was shown to cause cell cycle arrest, and to induce senescence in lung cancer A549 cells.…”
Section: Cytotoxic and Antitumor Promoting Activitymentioning
confidence: 99%
“…In contrast, higher activity was observed for the extract against human papillomavirus (HPV), which plays a pivotal role in the development of cervical cancer [87]. The butanol-soluble fraction of an ethanolic extract of fresh B. delagoense plants showed antiproliferative activity [88] in several cell lines via a modulation of the mitotic cell division. More recently, the water-soluble fraction of the same extract was shown to cause cell cycle arrest, and to induce senescence in lung cancer A549 cells.…”
Section: Cytotoxic and Antitumor Promoting Activitymentioning
confidence: 99%
“…Clinical studies have suggested relationships between visceral cancers, heart diseases, and abnormalities of the tongue and its coating [2-4]. However, the current practice in TCM is mainly subjective, and the quality of the visual inspection varies among medical professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbed metaphase may be the result of disturbances in the spindle apparatus or due to inhibition of spindle formation (Hsieh et al 2012;Cuyacot et al 2014;Tripathy and Rao 2015). Adam and El-Ashry (2010) attributed macro and micro cells to the failure of normal organization and function of spindle apparatus.…”
Section: Discussionmentioning
confidence: 99%